Prognostic factors of mortality in elderly with community acquired pneumonia - Đordjević Ivanka; Pejčić Tatjana; Stanković Ivana; Golubović Slavica; Ćirić Zorica (Vojnosanitetski Pregled)
Background/Aim. Community acquired pneumonia in elderly has specific clinical aspect and higher mortality in relation to younger patients. According to specific pneumonia severity assessment on admission and its importance in proper prediction of clinical course and outcome, the aim of this study was defining prognostic factors of mortality. Methods. This study included 240 patients aged ≥ 65 years with community acquired pneumonia. On admission, demographic characteristics, underlying diseases, physical symptoms and findings, laboratory values, chest radiography and oxygen blood saturation (SaO2) were analyzed. Multivariate analysis was used to identify characteristic prognostic factors which showed a statistical significance in relation to mortality. Results. Altered mental status, respiratory frequency ≥ 23/min and the presence of bilateral pneumonic infiltrates were defined as the most important prognostic factors of mortality (p < 0.001). These factors displayed 57.89% sensitivity, 100% specificity and 93.33% accuracy. Conclusion. The presence of identified characteristic prognostic factors on admission pointed out an adverse clinical course and outcome of community acquired pneumonia in elderly. Age and sex were not significantly associated with mortality.